KETERAMPILAN MANAJERIAL KEPALA MADRASAH/SEKOLAH DALAM MENINGKATKAN MUTU LULUSAN - Walid, Muhammad (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2008)
Managerial skill is an ability to perform a job base on a competence in which is done by objective and in collaboration with others. In education, leader’s skill of school as manager is an ability of school leader to do a tasks base on the ability competence in leading the objective through t he others. Whereas, the school leader who has the competence is getting of best of a work qualification that is agree with a work and in reality. The school leader who has a competence be able to do in his job effectively and efficiently. There are tree managerial skills those should be dominated by school leader: conceptual skill, technical skill, and skill for dealing with others. Keyword: Manajerial Skill, Madrasah, Quality.